2021
DOI: 10.1152/ajpgi.00408.2020
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical necrotizing enterocolitis-induced systemic immune suppression in neonatal preterm pigs

Abstract: Preterm infants are at high risks of sepsis and necrotizing enterocolitis (NEC). Some develop sepsis shortly after suspected or confirmed NEC, implying that NEC may predispose to sepsis but the underlying mechanisms are unknown. Using NEC-sensitive preterm pigs as models, we investigated the immune status in animals following development of sub-clinical NEC-like lesions with variable severities. Caesarean-delivered preterm pigs were reared until day 5 or 9. Blood was analyzed for T cell subsets, neutrophil pha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
1
5
1
Order By: Relevance
“…In contrast to the healthy preterm piglets, the preterm piglets that developed NEC showed a different pattern. In these NEC piglets, the mucus barrier was unable to trap and confine the NPs (large pathogen model compound), which was consistent with higher levels of bacteria adhering to the NEC intestinal mucosa and increased expression levels of innate inflammatory cytokines ( IL6 and IL8 ), as previously reported 34 , 45 . However, we did not observe any significant differences in goblet cell density or gene expression of the predominantly intestinal gel-forming mucin, MUC2 , in the NEC piglets.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In contrast to the healthy preterm piglets, the preterm piglets that developed NEC showed a different pattern. In these NEC piglets, the mucus barrier was unable to trap and confine the NPs (large pathogen model compound), which was consistent with higher levels of bacteria adhering to the NEC intestinal mucosa and increased expression levels of innate inflammatory cytokines ( IL6 and IL8 ), as previously reported 34 , 45 . However, we did not observe any significant differences in goblet cell density or gene expression of the predominantly intestinal gel-forming mucin, MUC2 , in the NEC piglets.…”
Section: Discussionsupporting
confidence: 87%
“…This suggests that the amount of mucins does not differ in the NEC condition and that other factors such as mucus composition and mucin PTM structure may regulate the mucus barrier instead. Although the NEC condition in our preterm piglets corresponds to a more sub-clinical NEC condition than in human infants 34 , we found that the mucus barrier was significantly impaired by this sub-clinical NEC state. This indicates that the mucus barrier may be an important factor in the NEC condition.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…On this background, it is not surprising that 10-30% of very preterm infants develop immune-related disorders such as NEC and LOS and that many organ complications in preterm infants are partly related to dysregulated local host immune responses to infection/ inflammation. Hyper-inflammatory conditions like NEC and LOS may also induce immunosuppression, predisposing to secondary infection risks, as indicated by infant studies (16) and blood cell transcriptome and immune studies in preterm pigs with NEC (17,18).…”
Section: Transition At Birth and Postnatal Immune Developmentmentioning
confidence: 99%